Two-Stage Series Model Predictive Torque Control for PMSM Drives - Zhang, Xiaoguang; Yan, Kang; Cheng, Ming (IEEE transactions on power electronics, 2021)
A two-stage series model predictive torque control for permanent magnet synchronous motor drives is proposed in this article. First, the control of torque and flux linkage is converted to double-torque control (i.e., the control of active torque and reactive torque) based on the instantaneous power theory to eliminate the weighting factor in conventional model predictive torque control. Then, the double-torque prediction trajectory and double-torque reference are extrapolated to two control periods. The concept of two-stage series predictive control is proposed in this article, in which the cost functions of two prediction instants are designed to form series control structure. In the proposed method, the first-stage prediction is used to select candidate voltage vectors and the second-stage prediction is used to evaluate the optimal voltage vector. Since the cost function of two control periods in the future is considered when selecting the voltage vectors, the possibility that the same voltage vector is applied to adjacent control periods increases, thereby reducing the switching frequency of the system. Finally, the effectiveness of the proposed method is verified by experiments.